G309 A systematic review of infant and young children complementary feeding practices in south asian families. (24th May 2017) - Manikam, L; Robinson, A; Lever, I; Kuah, JY; Vaidya, HJ; Alexander, EC; Miller, GW; Singh, KK; Dawe, V; Ahmed, S; Lingam, R; Prasad, A; et al.
Abstract : Aims: Sub-optimal nutrition among children remains a problem across South Asia (SA). Appropriate complementary feeding practices (CFP) can greatly reduce this risk. We aimed to undertake a systematic review of studies assessing CFP in SA children aged 0– 2 years in Bangladesh, India and Pakistan. Methods: Searches undertaken between January 1990 to June 2016; MEDLINE, EMBASE, Global Health, Web of Science, OVID Maternity and Infant Care, BanglaJOL, Cochrane Library, CINAHL, POPLINE and WHO Global Health Library. Eligibility criteria: primary research on CFP in SA children aged 0–2 years and/or their families. Search terms were: 'children', 'feeding' and 'Asians' with their derivatives. Two researchers undertook study selection, data extraction and quality appraisal (EPPI-Centre Weight of Evidence). Results: From 45, 712 studies identified, 126 descriptive studies (105 cross-sectional, 11 cohort, 8 qualitative, 1 case-control and 1 mixed studies) were included. 73 from India, 17 Pakistan and 36 Bangladesh. Despite each adopting WHO Infant and Young Children Feeding (IYCF) Guidelines, CFP were sub-optimal in all three countries. In Pakistan, of 15 studies reporting CFP timings, 8 recorded timely initiation (between 6–9 months). Of those reporting dietary diversity, 3 of 9 studies met minimum dietary diversity requirements across 4 of 7 WHO IYCF food groups. 2 of 3 studies observed minimum meal frequency in over 50% of participants. In India 35 of 59 studies reported timely initiation of CFP. 7 of 9 studies noted minimum dietary diversity achieved between 10%–23% of the study population. 5 of 15 studies noted minimum meal frequency achieved between 25%–96% of the study population. In Bangladesh, in 13 of 36 studies timely initiation of CFP ranged from 42%–64%. 3 of 17 studies noted minimum dietary diversity achieved between 19.8%–57.7% of the study population. 1 of 7 studies noted minimum meal frequency achieved between 33%–81% of the study population. Influencing factors included poor education about CFP, cultural beliefs and socioeconomic variables. Conclusion: This is the first SR to evaluate CFP in infants in India, Pakistan and Bangladesh. There is a great need for revision of nationwide child health programmes and campaigns to change health and nutrition behaviour.